Antisecretory and antioxidative effects of the antidepressants fluvoxamine and mirtazapine on water immersion stress and pyloric ligation-induced gastric ulcer in rats - Abdel-Hamed, Asmaa R.; Abo-Elmatty, Dina M.; Essawy, Soha S.; Taha, Mohamed A.; Huwait, Etimad A.; Alghamdi, Leena; AL-Ghamdi, Maryam A. (International Journal of Health Sciences, 2022)
Objectives: Although there are numerous drugs available for the treatment of gastric ulcers (GU), these drugs are not always effective. Antidepressant medications have been used for a variety of non-psychiatric indications, including antiulcer activity in various ulcer models. The purpose of this study was to compare the antiulcer effects of fluvoxamine and mirtazapine in two rat GU experimental models and to determine their relationship to antioxidant and antisecretory mechanisms. Materials and Methods: The antiulcer activities of various doses of fluvoxamine and mirtazapine on water immersion restraint stress (WIRS) and pyloric ligation-induced GU in rats have been studied against the positive control antiulcer drug famotidine. Various oxidative stress markers were evaluated. Results: Fluvoxamine and mirtazapine significantly protected against WIRS and pyloric ligation-induced gastric lesions, as evidenced by a dose-dependent decrease in ulcer index, myeloperoxidase (MPO) activity, lipid peroxidation, and an increase in prostaglandin E2, nitric oxide (NO), and reduced glutathione levels, as well as increased antioxidant enzyme activity. In the pyloric ligation model, fluvoxamine and mirtazapine improved GU more than famotidine. Furthermore, a 30 mg/kg dose of mirtazapine significantly improves both NO levels and MPO activity compared to famotidine. Conclusions: The results highlighted the relationship in correlating the antiulcer effect of drugs from different antidepressant classes across two animal GU models, implying that antidepressants that affected both norepinephrine and serotonin levels (mirtazapine) had a more potent antiulcer effect in WIRS-induced gastric model than drugs that only affected serotonin levels (fluvoxamine).